2010
DOI: 10.1371/journal.pone.0012197
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Profiles and Their Relationship with Cytogenetic Status in Adult Acute Myeloid Leukemia

Abstract: BackgroundAberrant promoter DNA methylation has been shown to play a role in acute myeloid leukemia (AML) pathophysiology. However, further studies to discuss the prognostic value and the relationship of the epigenetic signatures with defined genomic rearrangements in acute myeloid leukemia are required.Methodology/Principal FindingsWe carried out high-throughput methylation profiling on 116 de novo AML cases and we validated the significant biomarkers in an independent cohort of 244 AML cases. Methylation sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 38 publications
4
59
0
Order By: Relevance
“…Interestingly, we and others have previously identified aberrant DNA methylation of Wnt antagonists as being responsible for the activation of the Wnt/b-catenin pathway required for the development of leukemic stem cells and for the maintenance of self-renewal on AML1-ETO patients. 37 This study reveals another level of complexity identifying the H3K9me3 modification as an initial event targeting this pathway (TCF3, SOX18 or FZD7) in the HSPC-AE model. SUV39H1 is the only member of the mammalian H3K9 histone methyltransferases known to interact with AML1 and DNA methyltransferase 1.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, we and others have previously identified aberrant DNA methylation of Wnt antagonists as being responsible for the activation of the Wnt/b-catenin pathway required for the development of leukemic stem cells and for the maintenance of self-renewal on AML1-ETO patients. 37 This study reveals another level of complexity identifying the H3K9me3 modification as an initial event targeting this pathway (TCF3, SOX18 or FZD7) in the HSPC-AE model. SUV39H1 is the only member of the mammalian H3K9 histone methyltransferases known to interact with AML1 and DNA methyltransferase 1.…”
Section: Discussionmentioning
confidence: 78%
“…36 We recently showed that the AML1-ETO fusion protein was not sufficient to induce the specific DNA methylation pattern observed in primary patient samples. 37 The AML1-ETO fusion protein is known to repress transcription by recruiting chromatin modifiers such as the NCoR/SMRT/HDAC complex, 10 thus leading to histone H4 deacetylation and recruitment of the SUV39H1 protein, a histone H3 lysine 9 methyltransferase at DNA binding sites. 38 Using ChIP-chip, we identified 1168 AML1-ETO target genes involved in functions such as hematopoietic differentiation and self-renewal, the main features reported in the HSPC-AE.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies showed associations of certain methylation patterns with specific chromosome abnormalities and gene mutations and suggested a prognostic significance to these patterns. [3][4][5][6][7][8][9][10][11][12] However, it remains unclear if DNA methylation profiles differ according to AML cytogenetic risk group, the principal predictor of outcome in AML.…”
Section: Introductionmentioning
confidence: 99%
“…For the PCSs, the risk of bias assessments ranged from low 24,30,101,193,395 to low to moderate. 34,127,394 None of those studies were found to have methodological flaws that would raise concerns about the studies' findings. Refer to Supplemental Table 19 for the quality-assessment results of studies included for statement 20.…”
mentioning
confidence: 99%
“…398 target genes was associated with better progression-free survival and OS in cytogenetically normal AML. 399 Within our SR, 2 studies were identified for gene-specific methylation, one finding no significant prognostic effect of BMP/ retinoic acid inducible neural specific 1 (BRINP1/DBC1) methylation in AML 394 and one of which found that methylation status of any of 9 specific genes adversely affected OS in ALL (P , .05). 34 In our SR, 5 studies found a significant effect of miRNA expression levels on outcome in adult AML (P , .05), 24,30,127,193,395 including one in which miRNA expression patterns were correlated with expression of other prognostic markers, 127 whereas one study found no significant effect on outcome.…”
mentioning
confidence: 99%